A MORE FUNDAMENTAL APPROACH TO PREDICT PORE PRESSURE FOR SOFT CLAY - A. S. Balasubramaniam; E. Y. N. Oh; C. J. Lee; S. Handali; T. H. Seah (International Association of Lowland Technology, 2007)
Skempton’s (1954) pore pressure coefficient A provides a pragmatic attempt at determining pore pressures during undrained shear, and to use these in settlement computations and stability analysis of embankments in soft clays. Also, the Critical state concept offers a means of acquiring the undrained stress path in normally consolidated clays through using a volumetric yield locus derived from a simple energy balance equation. However, to date there is no novel method by which the undrained stress paths of lightly over-consolidated and heavily overconsolidated clays can be predicted by using fundamental concepts. Based on the work of Handali (1986), Balasubramaniam et al. (1989) presented an alternative pore pressure coefficient that was more generalised than the Skempton’s coefficient. However, Pender (1978) proposed a set of parabolas to describe the undrained stress paths of overconsolidated clays, and Lee (1995) considered elliptic paths to be more in agreement with the experimental observations. In this paper, observed and predicted undrained stress paths both under compression and extension, and also from isotropic and K0 pre-shear consolidation states will be presented. Such expressions can then be readily used in computer softwares for stability analysis and settlement computations.